Example of a microbiological criterion (MC) for verifying the performance of a food safety control system: Campylobacter Performance Target at end of processing of broiler chickens. (December 2015) - Lee, Judi; Castle, Marion; Duncan, Gail; Hathaway, Steve; van der Logt, Peter; Wagener, Sharon; LassoCruz, Amanda; Gichia, Moses; Tebwe, Tebikau; Silva, Ualesi
Abstract: New Zealand has focused on improving the food safety control systems for slaughter and dressing of broiler chickens in order to get a reduction in Campylobacter levels on carcasses at the end of primary processing. Each processor decides which good hygienic practice-based and hazard-based control measures to apply. Codex guidelines provide valuable information to assist with these decisions. To verify that the resulting control systems are effective, New Zealand established a microbiological criterion for Campylobacter which is applied after slaughter and dressing and initial chilling of broiler chickens. New Zealand calls this a regulatory Campylobacter Performance Target (CPT). Samples are tested by a direct plate enumeration method. Results are analysed using a "moving window approach" to aid data interpretation and decision-making. A "moving window limit" failure occurs when the log count for seven or more out of 45 samples in the moving window are greater than the established target of 3.78 log10  cfu/carcass. If processors meet the "target" this verifies that their process is under control. If processors fail the "target" they are expected to take corrective actions to restore control. If the processor's actions do not restore control in a timely fashion, the regulator applies further controls. This example is based on actual data from New Zealand poultry processers. The application of this microbiological criterion is flexible and other countries may be able to adapt this approach to suit their particular circumstances. Highlights: The Campylobacter Performance Target is a hazard-based microbiological criterion. The target is applied by the poultry industry. The target is intended to reduce the amount of Campylobacter on fresh chilled chicken meat. Results are interpreted by use of a moving window. A positive and related impact on the reduction of human cases of campylobacteriosis can be expected.